2020
DOI: 10.21511/ppm.18(2).2020.32
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Industry 4.0 on labor productivity in the Slovak Republic

Abstract: The Fourth Industrial Revolution bears major technological, demographic, and socio-economic changes affecting nearly every area in business. Within the human resources area, both a surplus of labor and the creation of brand new professions are to be expected. Industry 4.0 concept significantly affects labor productivity in individual countries and does not miss the Slovak Republic either. All segments of the labor market, not just industrial enterprises, will be affected. The present study aims to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Our analysis came to similar results as the analysis of the labor productivity at Slovakia in the context of the implementation of Industry 4.0, which also concluded that Slovakia is showing increasing economic output, increasing GDP, as well as increasing labor productivity. The contribution of Industry 4.0 is identified in industrial production, where it has the greatest potential for increasing labor productivity, but also the creation of new jobs (Grencikova, Kordos, & Berkovic, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis came to similar results as the analysis of the labor productivity at Slovakia in the context of the implementation of Industry 4.0, which also concluded that Slovakia is showing increasing economic output, increasing GDP, as well as increasing labor productivity. The contribution of Industry 4.0 is identified in industrial production, where it has the greatest potential for increasing labor productivity, but also the creation of new jobs (Grencikova, Kordos, & Berkovic, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The development of both analyzed economies and further technological investments creates opportunity to maintain prosperity and high level of production and consumption, despite ageing population and in more ecologic economy [15]. The growth of GDP and labor productivity as the benefits of Industry 4.0, and identification of the area of industrial production as an area with huge potential for development has been identified for Slovak economy [16].…”
Section: Discussionmentioning
confidence: 99%
“…The research on impacting of Industry 4.0 on employees was carried out by such scientists as Sumer (2018), Nafchi andMohelská (2018), andFreddi (2018). Grencikova et al (2020) showed that although the labor force within the Slovak labor market will not increase, the labor force will decrease due to unfavorable demographic development. The overall productivity in Slovak companies will increase due to the new technologies implementation.…”
Section: Literature Reviewmentioning
confidence: 99%